Research for universal health coverage. (World health report., 2013)
Everyone should have access to the health services they need without being forced into poverty when paying for them. This report argues that universal health coverage - with full access to high-quality services for prevention treatment and financial risk protection - cannot be achieved without the evidence provided by scientific research. It maintains that all nations should be producers of research as well as consumers. The process of discovery should take place not only in academic centres but also in public health programmes where people seek health care and use the services provided. Inves.